Patients’ choice of healthcare provider for primary hip and knee arthroplasty: a national register-based observational cohort study of 62,676 patients from Norway, 2014–2018 - Beate Hauglann; Cato Kjærvik; Eva Stensland; Yohannes Tesfay; Anne Marie Fenstad; Ove Furnes; Tor Ingebrigtsen (Acta Orthopaedica, 2026)
Background and purpose: We aimed to quantify how provider-related factors are associated with patients’ revealed, GP-mediated choice of arthroplasty provider in Norway, expressed as willingness to travel (WTT) in minutes, and to explore how WTT for travel time was modified by patient characteristics.Methods: This is a national observational cohort study including all publicly funded, elective primary hip and knee arthroplasties in Norway, 2014–2018 (n = 62,676), with linkage to national registries. A mixed logit model was used to analyze choice among providers with different attributes, in both preference and WTT space. Associations between individual-level travel-time preferences and patient characteristics were analyzed with multilevel modelling.Results: Patients accepted substantial additional travel time for several provider attributes. Mean WTT was 156 min (95% confidence interval [CI] 130–182; median 8) for a dedicated elective surgical unit, 70 min (CI 67–72) for a provider within the patient’s regional health authority, 16 min (CI 15–17) for above-median surgical volume, 4 min (CI 3–5) for an adult child living near the provider, and 3 min (CI 3–3) for below-median waiting time. WTT for travel time was reduced in patients with high comorbidity (−27%), low education (−33%), and low income (−30%), with graded gradients across categories, and decreased with increasing age.Conclusion: Provider attributes were associated with patients’ revealed, GP-mediated choice of arthroplasty provider, expressed as clinically interpretable WTT. WTT was lower among older, sicker, and socioeconomically disadvantaged patients, indicating that realized choice is patterned by both modifiable structural features of the healthcare system and patient-level socioeconomic gradients.